Risky Behaviour Among Adolescents - Greš, Alen; Staver, Dijana; Šakić, Branislav; Radovančević, Ljubomir (Scripta Medica, 2023)
Background/Aim: Nowadays, adolescents are exposed to some negative challenges. Bullying is one of the horrible phenomena that can be seen in the physical and mental harassment of children and teenagers. Another challenge is addiction to computer games as well as writing on social networks. Gambling addiction, habituation and exposure to psychostimulants are also a trap for causing severe pathology. The aim of this study was to present an insight into the possible challenges of nowadays to which adolescents are exposed and how they affect their personality and maturation. Methods: The authors collected data and materials on the mentioned topics from their daily medical work. They also used articles in professional magazines and newspapers and television shows. Results: Society must make efforts to eradicate such events in schools. We are witnessing various challenges and pitfalls that affect youth, society, culture and civilisation. Among the bad things, drug addiction, alcoholism, smoking, addiction to the Internet and computer games are in the first place. Conclusion: Due to negative challenges, the youth neglect their schoolwork and duties. The school environment can be a place for violent behaviour, brachial attacks (bullying and harassment). Recognising social interactions, family relationships and understanding the underlying psychiatric conditions which may be associated with risky behaviour in adolescents could be essential for treatment planning.
Keywords: Adolescent; Risky behaviour; Social networks; Today's society